Patients' perception of community pharmacists as healthcare providers and willingness to participate in pharmacist services: a pilot study. Issue 4 (17th April 2018) - Ekenga, Vincent; Bailey-Wheeler, Janel; Sarpong, Daniel; Hart, Tammy; Earls, Martha
Abstract: Objectives: To explore the extent to which patients identify community pharmacists as healthcare providers and the relationship of this perception to a willingness to engage in pharmacist-provided services. Methods: A cross-sectional survey was conducted at a retail pharmacy and a patient-centred medical home (PCMH) in the New Orleans, Louisiana metropolitan area. The survey assessed patients' perception of community pharmacists and their roles in the provision of health care, as well as willingness to participate in commonly offered pharmacist-provided services. Key findings: This study included 49 participants who interacted with pharmacy personnel to receive prescriptions regularly. Of the 49 patients surveyed, 91.8% perceived community pharmacists to be healthcare providers, and this perception significantly impacted patient willingness to participate in medication therapy management, medication optimization and travel vaccination services. Other services were not significantly impacted by perception. Conclusion: A greater percentage of patients perceived community pharmacists as healthcare providers. This affirmative perception positively impacted patient willingness to participate in several pharmacist-provided services. As no comparative studies are available, further study is needed to assess consistency of observations and assess innovative ways to highlight pharmacists' cognitive attributes and increase participation in pharmacist-provided services.